The Medical Informatics Initiative and the Network University Medicine - Perspectives for Nuclear Medicine - Miederer, Isabelle; Rogasch, Julian Manuel Michael; Fischer, Regina; Fuchs, Timo; Lapa, Constantin; Lohmann, Philipp; Shi, Kuangyu; Tran-Gia, Johannes; Wendler, Thomas; Hellwig, Dirk (Nuklearmedizin - NuclearMedicine, 2023)
Digitization in the healthcare sector and the support of clinical workflows with artificial intelligence (AI), including AI-supported image analysis, represent a great challenge and equally a promising perspective for preclinical and clinical nuclear medicine. In Germany, the Medical Informatics Initiative (MII) and the Network University Medicine (NUM) are of central importance for this transformation. This review article outlines these structures and highlights their future role in enabling privacy-preserving federated multi-center analyses with interoperable data structures harmonized between site-specific IT infrastructures. The newly founded working group “Digitization and AI” in the German Society of Nuclear Medicine (DGN) as well as the Fach- und Organspezifische Arbeitsgruppe (FOSA, specialty- and organ-specific working group) founded for the field of nuclear medicine (FOSA Nuklearmedizin) within the NUM aim to initiate and coordinate measures in the context of digital medicine and (image-)data-driven analyses for the DGN.
Keywords: Digitalization; Data integration; Harmonization; Federated learning; Multi-centric analysis